Spatial distribution of Bertholletia excelsa in selectively logged forests of the Peruvian Amazon. (9th January 2017) - Rockwell, Cara A.; Guariguata, Manuel R.; Menton, Mary; Quispe, Eriks Arroyo; Quaedvlieg, Julia; Warren-Thomas, Eleanor; Silva, Harol Fernandez; Rojas, Edwin Eduardo Jurado; Arrunátegui, José Andrés Hideki Kohagura; Vega, Luis Alberto Meza; Hancco, Roger Quenta; Vera, Olivia Revilla; et al.
Abstract: To date, the spatial distribution pattern and density of Brazil nut trees in logged forest stands is unclear across the Amazon basin. We asked the following questions: (1) What are the densities and spatial distributions of Brazil nut juveniles (10 ≤ dbh < 40 cm) and adults (≥ 40 cm dbh) in three selectively logged Brazil nut concessions (1413 ha sampled) in Madre de Dios, Peru; (2) What is the spatial relationship between adults and juveniles (10 ≤ dbh < 30 cm); and (3) What is the spatial relationship between juveniles (10 ≤ dbh <30 cm) and cut stumps (≥ 10 y)? Spatial analyses were conducted using statistics derived from Ripley's K function. Juveniles were aggregated in all three concessions. Results for adult populations rejected the null hypothesis of a random distribution among trees ≥ 40 cm dbh. We did not find an attraction between juveniles and cut-stump locations, nor between adults and juveniles. The strong peaks of aggregation for juveniles and adult Brazil nuts in this study occurred at long distances (300–900 m), suggesting multiple tree canopy gaps as drivers of spatial distribution patterns, either via natural or anthropogenic sources. Our data contribute to a more thorough understanding of Brazil nut population structure in disturbed forests in south-western Amazonia.